POMFRET FISHERY OF INDIA WITH SPECIAL REFERENCE TO THE CATCH STATISTICS OF MAHARASHTRA AND GUJARAT COASTS - Prasannakumari, B; Dharmaraja, S K (Indian Journal of Fisheries, 2011)
The pomfrets constitute about 2.32% of the total marine fish production inIndia. The bulk of the catch comes from Maharashtra and Gujarat States, whichjointly contribute to about 61% of the total all India pomfret landings. The fishingseason for pomfret fishery in the States of Maharashtra and Gujarat and the gearsemployed for the exploitation of the fishery in these States are given.